Kualitas Hidup Pasien Pasca Serangan Stroke - I Dewa Putu Gede Putra Yasa; VM Endang SP Rahayu (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
The purpose of this qualitative, descriptive Phenomenology study was to enhance understanding about quality of life after a stroke from the patient's own perspective. The study is located at internal outpatient ward of General Sanglah Hospital with five participants were selected by using porpusive sampling method. Data were gathered through indeft interview with each participant on October 2012. The study finding four themes as follow: disable to activity daily living, Suffering emerges amid unaccustomed restrictions and losses, emotional response of social isolation after stroke attack and stroke patients need the health service professional.